COMPREHENSIVE MIDWIFERY CARE FOR SLEEP DISTURBANCES IN A MULTIGRAVIDA PATIENT : - Rostiana, Vina; Oktri, Yosi (STIKes Budi Luhur Cimahi, 2024)
In the third trimester, women usually experience discomfort such as low back pain, frequent urination, fetal movements, heartburn, leg cramps, fatigue, especially sleep disturbances or difficulty sleeping until the morning. Third trimester pregnant women often experience sleep disturbances, this causes a decrease in sleep duration in pregnant women. Based on the Ministry of Health of the Republic of Indonesia, in 2021, the number of pregnant women in Indonesia who experienced sleep disorders reached 64%. This study aims to determine midwifery care to overcome sleep disorders in pregnant women. The method in this research is a case study approach. Data collection in this research used interviews and observation. The subject of this research was Mrs